Strange Stories from the Lodge of Leisures - Pu, Songling, 1640-1715; Soulié de Morant, G. (Georges), 1878-1955 (Salt Lake City, UT : Project Gutenberg, 2011)
"Strange Stories from the Lodge of Leisures" by Pu Songling is a collection of Classical Chinese stories written over forty years from the late 1600s to early 1700s. This anthology contains nearly 500 tales blending the supernatural with everyday reality, exploring passionate emotional entanglements between humans and otherworldly beings. These marvel tales blur boundaries between realms through vivid detail, using ghosts, foxes, and demons to implicitly critique societal problems. The work circulated in manuscript form during the author's lifetime and became China's most acclaimed supernatural collection since the Ming dynasty. (This is an automatically generated summary.)
The ghost in love -- The fresco -- The dwarf hunters -- The corpse of the blood-drinker -- Love rewarded -- The woman in green -- The fault and its consequences -- Deceiving shadows -- Peaceful-light -- Hong the currier -- Autumn-moon -- The princess Nelumbo -- The two brothers -- The marble arch -- The dutiful son -- Through many lives -- The river of sorrows -- The mysterious island -- The spirit of the river -- The devils-of-the-ocean -- Unknown devils -- Childless -- The patch of lamb's skin -- Love's-slave -- The laughing ghost.
Wikipedia page about this book: https://en.wikipedia.org/wiki/Strange_Tales_from_a_Chinese_Studio
Release date is 2011-10-16
David Starner, Matthew Wheaton and the Online Distributed Proofreading Team
Keywords: Ghost stories, Chinese; Chinese fiction -- Translations into English